Students of Bachelor of Technology in Computer Science, School of Computer Science Engineering, Galgotias University, Greater Noida. (International Journal of Engineering and Computer Science, 2017)
Currently Cloud Computing is fastly growing area in IT world. It provide physical and virtual resources to the users as pay per uses bases. Now a days users of cloud are increasing day by day so to handle a lots of data and tasks are difficult. That’s why proper allocation of tasks to resources is very important factor in cloud computing. Here this paper define an algorithm using K-mean clustering technique for task scheduling in cloud for better outcomes.